THE ANALYSIS OF CODE-SWITCHING IN X JAPAN'S SONG - Astowo, Cesar SWF; Inderawati, Rita (English Community Journal, 2025)
This study analyzes the phenomenon of code-switching in the lyrics of six songs by the Japanese rock band X Japan: Dahlia, Scars, Longing, Rusty Nails, Tears, and Forever Love. Employing a qualitative descriptive approach, the research identifies and categorizes code-switching into three types: intersentential, intrasentential, and tag switching. The research instrument played an important role in obtaining the research results. Creswell (2009, p. 164) stated that in qualitative research, the main instrument was the researcher. The researcher uses some steps in analyzing the data, which are, first observing the data or information available in the data sheet, second classifying the data based on the kinds of code-switching used, third recheck and make sure all the data is well organized. Describing and discussing the code-switching used, and last drawing a conclusion based on the data analyzed. A total of 123 instances of code-switching were identified, with tag switching being the most prevalent (46%), followed by intersentential (37%) and intrasentential switching (17%). The analysis indicates that English insertions enhance rhythm, emphasize emotion, and broaden the appeal to an international audience. These findings underscore the linguistic creativity within J-Rock music and imply that code-switching fulfills both artistic and communicative functions within multilingual song lyrics.